The Effect of Home Hand Exercise on Joint Pain and Range of Motion in Patients with Rheumatoid Arthritis: A Randomized Clinical Trial - Delkash, Parisa; Salehi, Shahin; Abozarzadeh Tahamtan, Niloofar (Novelty in Biomedicine, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by persistent joint inflammation, pain, and reduced functional capacity. Hand involvement is one of the most common and debilitating manifestations of RA, leading to progressive stiffness, weakness, and limited range of motion. While pharmacological treatments remain the cornerstone of RA management, non-pharmacological interventions such as therapeutic exercises have gained attention for their potential benefits. However, evidence on the effectiveness of home-based hand exercises in improving pain and joint function remains limited. Materials and Methods: A randomized controlled trial (RCT) was conducted at Imam Hossein Hospital in Tehran, Iran, from 2023 to 2024. A total of 154 RA patients were enrolled and randomly assigned to either the intervention group (n = 77), which received standard pharmacological treatment along with a structured home-based hand exercise program, or the control group (n = 77), which received only standard pharmacological treatment. The intervention lasted four weeks, during which patients in the exercise group performed specific hand exercises designed to improve joint mobility and grip strength. Pain intensity was assessed using the Visual Analog Scale (VAS), while range of motion (ROM) and hand grip strength were measured using a goniometer and a dynamometer, respectively. Baseline and post-intervention assessments were compared within and between groups. Results: Both groups experienced a significant reduction in pain intensity after four weeks (P < 0.001). However, the difference in VAS score reduction between the intervention and control groups was not statistically significant (P = 0.870). Hand grip strength significantly improved in both the right and left hands in the intervention group compared to the control group (P<0.001). Additionally, ROM in flexion and extension significantly increased in both hands in the intervention group, whereas no significant improvements were observed in the control group (P<0.001). Conclusion: Home-based hand exercise therapy effectively improved hand grip strength and joint mobility in RA patients, although it did not result in a statistically significant reduction in pain compared to standard treatment alone. Given its accessibility and potential benefits, integrating structured hand exercises into routine RA management is recommended to enhance functional outcomes and promote patient independence. Further studies with longer follow-up periods are needed to assess the sustainability of these benefits.